Efectos de una segmentación del impuesto al valor agregado en Ecuador periodo 2012 - Pérez Vásconez, Adams Víctor (2015)
Taxes are part of our everyday living, are related in any commercial activity and market decisions from the stages of production through acquisition personal use or consumption. Undoubtedly taxes are an axis for each government, as its revenue helps support public spending, despite this, there is disagreement on the part of those who contribute to these payments, particularly in the case of final consumers by difficulty to display a direct and immediate compensation for their amounts. The State pays the amount collected through public works, however, the tax burden determined and assumed by each individual, taxpayer or person is not differentiated or consider the level of economy and rates of tax capacity. Given the above it is desired to clarify a little this perception of the contribution of IVA in Ecuador through the effects they would have major economic activities that integrate and streamline the subjects that. In the first chapter of this contribution are definitions of IVA, its history in Ecuador and rates in Latin America. In the second chapter issues that contribute to the development of the categorization of IVA rates and methods for analyzing the observed data they are presented. In the third chapter arise parameters to determine which activities are subject to exchange rate elasticities are analyzed and as a complement to the study, a survey was conducted. Chapter 4 details the results for the proposed changes in IVA, the relationship between the study variables and analysis of the survey which shows the payment of taxes is driven at a reduced rate from 12% to 10% as parallel markets are an option for consumers to increase IVA.